Entrepreneurship: a foucauldian analysis of enterprise development and the Post-Apartheid subject - Beilings, Christopher (My University, 2019)
Set in the context of a post-Apartheid South Africa, this research report constitutes a Foucauldian analysis of how state institutional support for SMME resonates with neoliberal governmentality and the consequent attempt to prompt the post-Apartheid subject. Relevant herein, are the state institutions that are mandated to further the states initiative of enterprise development. Primarily making use of archival analysis, policy data from these institutions were sought out and analysed. Analysing enterprise development from a historical perspective, it is evident that intentions have evolved with regard to two factors. Firstly, the ever-permeating growth in the promotion of ‘entrepreneurial culture’; and secondly, the differentiation of targeted subjects. Through studying these findings, it is argued that there is an attempt by the state to condition entrepreneurial subjectivities. It can further be argued that, as a consequent to the former, the agenda of the state is to outsource fiscal liabilities to informal markets. This research report ultimately constitutes a Foucauldian interpretation of these two cardinal findings.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Artsin Political Studies by Creative Writing to the Faculty of Humanities, University of the Witwatersrand, March 2019
Keywords: Foucault, Michel--1926-1984--Criticism and interpretation; Government business enterprises; Entrepreneurship